Recomposição de reserva legal na região do tapajós: identificação de espécies e sistemas silviculturais - VIEIRA, Luiza de Sousa (Universidade Federal do Pará, 2015)
This research had the goal to identify the potential species and arrangements and / or silvicultural systems, that associated to the spontaneous vegetation, ensure viable characteristics to the recomposition of Legal Reserve in the region of Tapajós. It was implanted three silvicultural systems: 1) Plantation of trees in plats of 36 plants per specie, in random blocks, 32 species that are the treatment, five repetitions, spacing 1,5 x 1,5. 2) Plantation in One Tree Plot - OTP, in random blocks, 29 species as treatment, 12 repetitions, spacing 3 x 3. 3) Plantation in agroforestry system, which was used the Taungya System, spacing 7 x 7. It was performed the characterization of the floristic composition, diversity and similarity of the spontaneous vegetation; measured the survival and growth of the Forest species; and productivity of the spontaneous vegetation and the planted forest species. In all the studies area, it was identified 1597 subjects belonging to 137 species, 98 gender e 40 families. The found Shannon - Weaver Index was 3,75 to plat, 3,72 to agroforestry e 3,56 to OTP. The similarity by the Sorensen Index found was: 65,52% between Plat and OTP, 63,58% between Plat and Agroforestry and 50,31% between OTP and Agroforestry. Considering the survival rate and the average growth in DAP e total height, the descending order of importance of the studied silvicultural systems was as follows: OTP 76 > OTP 75 > Plat 76 > Plat 75. For exploration of the Legal reserve area, considering the productivity of the subjects with DAP > 0,45m, the descending order of importance of the silviculturals systems is as follows: OTP > Plat > Agroforestry. As there were no statistically significant differences between the Shannon - Weaver Indexes found for the spontaneous vegetation of the three analyzed silvicultural systems, and considering the productivity of individuals with DAP > 0.45 m, the OTP system would be more indicated for the recovery of Legal Reserve specifically from the forest point of view and agroforestry system, although with less forest productivity could be indicated for the small producers because it is associated with agricultural crops..The study results show that around 40 years after the plantation of the Forest species in the referred agroforestry systems its possible obtain high diversity in floristic composition under these plantations, restoring the ecological and productive function of the area.